Intelligent Systems Design and Applications 17th International Conference on Intelligent Systems Design and Applications (ISDA 2017) held in Delhi, India, December 14-16, 2017 - Abraham, Ajith; Muhuri, Pranab Kr.; Muda, Azah Kamilah; Gandhi, Niketa; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
This book highlights recent research on intelligent systems design and applications. It presents 100 selected papers from the 17th International Conference on Intelligent Systems Design and Applications (ISDA 2017), which was held in Delhi, India from December 14 to 16, 2017. The ISDA is a premier conference in the field of Computational Intelligence and brings together researchers, engineers and practitioners whose work involves intelligent systems and their applications in industry and the real world. Including contributions by authors from over 30 countries, the book offers a valuable reference guide for all researchers, students and practitioners in the fields of Computer Science and Engineering.
Enhancing Job Opportunities in Rural India Through Constrained Cognitive Learning Process: Reforming Basic Education -- UML2ADA for Early Verification of Concurrency Inside the UML2.0 Atomic Components -- A New Approach for the Diagnosis of Parkinson's Disease Using a Similarity Feature Extractor -- A Novel Restart Strategy for Solving Complex Multi-Modal Optimization Problems using Real-Coded Genetic Algorithm -- Evaluating SPL Quality with Metrics -- Using Sentence Similarity Measure for Plagiarism Detection of Arabic Documents -- Computer Aided Recognition and Classification of Coats of Arms -- Mining Gene Expression Data: Patterns Extraction for Gene Regulatory Networks.
Keywords: Computational intelligence; Artificial intelligence; Computational Intelligence; Artificial Intelligence